2021
DOI: 10.3390/ani11082234
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed Supplementation Failed to Affect Fecal Microbiota and Metabolome as Well as Fecal IgA and Apparent Nutrient Digestibility in Adult Dogs

Abstract: The present study investigated in dogs the dietary effects of intact seaweeds on some fecal bacterial populations and metabolites, fecal IgA and apparent total tract digestibility (ATTD). Ten healthy adult dogs were enrolled in a 5 × 5 replicated Latin square design to evaluate five dietary treatments: control diet (CD); CD + Ascophyllum nodosum; CD + Undaria pinnatifida; CD + Saccharina japonica; CD + Palmaria palmata (n replicates per treatment = 10). Seaweeds were added to food at a daily dose of 15 g/kg. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Furthermore, dietary supplementation with 400 mg/kg seaweed-derived polysaccharides significantly increased the cecal concentrations of acetate and butyrate in weaned piglets [ 41 ]. However, dietary addition with seaweed had no effect on the SCFA composition and concentration in dog feces [ 19 ], which is consistent with our findings in kittens. In addition, we did not find an effect of S. boulardii on SCFAs in kitten feces.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, dietary supplementation with 400 mg/kg seaweed-derived polysaccharides significantly increased the cecal concentrations of acetate and butyrate in weaned piglets [ 41 ]. However, dietary addition with seaweed had no effect on the SCFA composition and concentration in dog feces [ 19 ], which is consistent with our findings in kittens. In addition, we did not find an effect of S. boulardii on SCFAs in kitten feces.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, research on the impacts of seaweed on pets is limited. A study showed that dogs fed a seaweed-supplemented diet exhibited no change in nutrient digestibility, fecal microbiota, and the metabolome [ 19 ]. Moreover, studies on the effects of seaweed on cat intestinal health have not yet been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…It can be conjectured that the present finding reflected the inclusion of AN, a rich source of soluble fibres (e.g., alginic acid, laminarin, and sulphated polysaccharides) [ 12 ] in the HP diet, which stimulated acetogenesis within the gut microbiota, as already reported in humans and pre-ruminants [ 64 , 65 ]. In sharp contrast, a recent investigation carried out in healthy dogs failed to demonstrate any influence on faecal L-SCFA profile when intact AN was supplemented at a dose of 15 g/kg of diet (as is) for a maximum of 28 days [ 66 ]. It must be stressed, however, that the level of AN fortification used in the present study was higher.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given the current knowledge about the importance of intestinal health for the whole organism, which reflects the general health of an individual, research evaluating the effects of different nutritional components on intestinal health has intensified in the last decade [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]; therefore, it was of paramount importance that the possible effects of coprophagy on these variables were investigated to assist researchers in choosing the most appropriate collection methods and ensure the accurate interpretation of results related to the variables measured in the present study.…”
Section: Discussionmentioning
confidence: 99%